Surface-Enhanced Raman Spectroscopy for Rapid Screening of Cinnamon Essential Oils. Issue 11 (November 2020) - Nelson, Patrick; Adimabua, Perculiar; Wang, Ankai; Zou, Shengli; Shah, Nilam C.
Cinnamon essential oil is used in food flavoring, food preservation, and for complementary medicine. The most common types of cinnamon used in essential oils are true cinnamon ( Cinnamomum verum ) and cassia cinnamon ( Cinnamomum cassia ). True cinnamon is commonly adulterated with cassia cinnamon because it is cheaper. However, cassia cinnamon contains higher concentrations of coumarin which has been shown to have adverse health effects. There is a need to develop simple, nondestructive, rapid screening methods for quality control and food authentication and to identify adulteration of cinnamon essential oil. Currently, the most common methods to screen for coumarin in cinnamon include high-performance liquid chromatography (HPLC) and gas chromatography (GC). However, these methods require time-consuming sample preparation and detection. Vibrational spectroscopy methods are emerging as a promising alternative for rapid, nondestructive screening for food safety applications. In this study, a rapid screening method has been developed to examine cinnamon essential oils using surface-enhanced Raman spectroscopy (SERS). The experimental spectra were compared to theoretical calculations using the DFT method BP86/6-311++G(d, p) basis set. The limit of detection of coumarin was determined to be 1 × 10 –6 M or 1.46 mg/L using SERS with colloid paste substrates. Furthermore, 1:16 dilutions of cinnamaldehyde and 1:8 dilutions of eugenol were detected using SERS which can help determine if the cinnamon essential oil was made from bark or from leaves. Seven commercially available cinnamon essential oils were also analyzed and compared to reference solutions. SERS was able to discriminate between essential oils primarily composed of cinnamaldehyde and those composed of eugenol. Furthermore, the SERS method detected peaks that are attributed to coumarin in two of the commercially available samples. To date, this is the first time SERS has been used to rapidly screen cinnamon essential oils.